Potential Use of Tuna (Thunnus albacares) by-product: Production of Antioxidant Peptides and Recovery of Unsaturated Fatty Acids from Tuna Head - Oliveira, Dayse; Bernardi, Daniela; Drummond, Fernanda; Dieterich, Fabiana [UNESP]; Boscolo, Wilson; Leivas, Carolina; Kiatkoski, Elaine; Waszczynskyj, Nina (Walter De Gruyter Gmbh, 2017)
Tuna by-products were subjected to enzymatic hydrolysis with Alcalase (enzyme to substrate ratio 1 : 200 w/w; 60 degrees C; pH 6.5, 120 min) rendering a tuna protein hydrolysate (TPH) with 9.24 % degree of hydrolysis (DH). The antioxidant capacity of TPH determined by the methods of ferric reducing antioxidant power (FRAP) and Trolox equivalent antioxidant capacity (TEAC) were similar and 10 times lower than the result obtained by oxygen radical absorbance capacity (ORAC). The total amino acid profile indicated that 42.15 % are composed of hydrophobic amino acids and 7.7 % of aromatics, with leucine being found in the highest quantity (17.85 %). The fatty acid profile of the oil recovered by centrifugation of the TPH - as determined by a gas chromatograph - was characterized by a high percentage of polyunsaturated fatty acids (PUFAs) (39.06 %), mainly represented by the fatty acids omega 3, docosahexaenoic acid (27.15 %) and eicosapentaenoic acid (6.05 %). The simultaneous recovery of unsaturated fatty acids and antioxidant peptides can add value to tuna by-products, assisting in the efficient management of fishing industry waste.
Keywords: amino acid profile; enzymatic hydrolysis; by-products; oxygen radical absorbance capacity; tuna